VALIDATION OF FLOOD INUNDATION DISTRIBUTION IN THE BORO WATERSHED USING SENTINEL-1 IMAGERY AND 1D HEC-RAS SIMULATION AGAINST FIELD OBSERVATION DATA - Bagus Ardian Saputra; Erni Mulyandari; Suryo Handoyo (JUMATISI: Jurnal Mahasiswa Teknik Sipil, 2026)
Flooding is a natural disaster that poses a serious problem in many regions of Indonesia, particularly in the Boro Watershed (DAS Boro), which experiences annual inundation in several urban villages. DAS Boro is a sub-watershed of the Bengawan Solo River, located in Jebres District, Surakarta City. Therefore, accurate flood management is necessary through disaster risk mitigation efforts. This study aims to identify flood inundation using Sentinel-1 satellite imagery visualization and hydraulic analysis through 1D modeling with HEC-RAS. The method applied is the HSS Snyder method with a two-year return period, calibrated using data from the Pepe Hilir Watershed. The analysis process began with site surveys and channel dimension measurements, along with field observations, including interviews with affected residents. Surveys were conducted at 19 points representing the inundated area. The area of DAS Boro was determined through data processing using QGIS 3.14.16, measuring 1.376 km², with a two-year flood discharge of 109.41 m³/s. The results show that flood visualization using Sentinel-1 achieved an accuracy (Recall) of 100% compared to data from BPBD and DPUPR Surakarta. Meanwhile, the HEC-RAS 1D model simulation reached only a 19.29% Recall rate, indicating that remote sensing approaches are more effective in identifying flood-affected areas.